The significance of regional planning - Černe, Andrej (Journal for Geography, 2008)
The article is a short summary of lectures at the 1st International Summer School GEOREGNET held at Faculty of Arts, University of Maribor in Maribor 23 September, 2008. The aim of the lecture was to discuss some of the basic dilemmas about the role of regional planning in a contemporary society within the context of market economy.
Keywords: regionalni razvoj; regionalno planiranje